2021
DOI: 10.1093/jpp/rgab074
|View full text |Cite
|
Sign up to set email alerts
|

β-Caryophyllene attenuates lipopolysaccharide-induced acute lung injury via inhibition of the MAPK signalling pathway

Abstract: Objectives Acute lung injury (ALI) is a pulmonary manifestation of an acute systemic inflammatory response, which is associated with high morbidity and mortality. Accordingly, from the perspective of treating ALI, it is important to identify effective agents and elucidate the underlying modulatory mechanisms. β-Caryophyllene (BCP) is a naturally occurring bicyclic sesquiterpene that has anti-cancer and anti-inflammatory activities. However, the effects of BCP on ALI have yet to be ascertained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…16 Others have likewise shown ameliorative effects for BCP in the treatment of acute lung injury induced by lipopolysaccharide in mice following reductions in several inflammatory markers, including TGFβ. 37 BCP also alleviated cerebral injury induced by ischemiareperfusion in rat as well as deterred lipid accumulation in human hepatocyte subsequent to enhancing the AMPK/ AKT signaling network in the targeted cells. 38,39 The present data agree with several earlier reports and advocate that BCP could be used as renoprotective agent against SFZ-induced renal injury by concurrently suppressing NF-κB and TGF-β1, and promoting renal antioxidant capacity via Nrf2-dependent pathways.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…16 Others have likewise shown ameliorative effects for BCP in the treatment of acute lung injury induced by lipopolysaccharide in mice following reductions in several inflammatory markers, including TGFβ. 37 BCP also alleviated cerebral injury induced by ischemiareperfusion in rat as well as deterred lipid accumulation in human hepatocyte subsequent to enhancing the AMPK/ AKT signaling network in the targeted cells. 38,39 The present data agree with several earlier reports and advocate that BCP could be used as renoprotective agent against SFZ-induced renal injury by concurrently suppressing NF-κB and TGF-β1, and promoting renal antioxidant capacity via Nrf2-dependent pathways.…”
Section: Discussionmentioning
confidence: 90%
“…16 Others have likewise shown ameliorative effects for BCP in the treatment of acute lung injury induced by lipopolysaccharide in mice following reductions in several inflammatory markers, including TGF-β. 37 BCP also alleviated cerebral injury induced by ischemia-reperfusion in rat as well as deterred lipid accumulation in human hepatocyte subsequent to enhancing the AMPK/AKT signaling network in the targeted cells. 38,39…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Similar effects were also shown after using BCP for attenuating sulfasalazine-induced renal damage that involved reductions in NF-κB and TGF-β alongside increased Nrf2, AMPK, and AKT concentrations [15]. BCP therapy also reduced lipopolysaccharide-induced acute lung injury in mice by decreasing a variety of inflammatory cytokines, including TGF-β [52]. Likewise, Ullah et al documented anti-inflammatory actions for BCP by suppressing TLR activity and upregulating the AMPK pathway in the nervous system [53].…”
Section: Discussionmentioning
confidence: 58%
“…β-Caryophyllene (BCP, CAS:87-44-5, trans -4,11,11-trimethyl-8-methylenebicyclo[7,2,0]undec-4-ene; Figure 1 A) is a naturally occurring bicyclic sesquiterpene compound that acts as a natural agonist of the CB2 receptor [ 18 ]. Previous studies have demonstrated that BCP inhibits the production of proinflammatory cytokines in immune cells [ 18 ] and exerts anti-inflammatory effects in vivo [ 19 , 20 ]. Based on these findings, we hypothesized that BCP, with its anti-inflammatory properties, might have beneficial effects when used as a topical therapeutic agent for AD treatment.…”
Section: Introductionmentioning
confidence: 99%